Evaluation of two different vaccine platforms for immunization against melioidosis and glanders - Biryukov, Sergei S.; Cote, Christopher K.; Klimko, Christopher P.; Dankmeyer, Jennifer L.; Rill, Nathaniel O.; Shoe, Jennifer L.; Hunter, Melissa; Shamsuddin, Zain; Velez, Ivan; Hedrick, Zander M.; Rosario-Acevedo, Raysa; Talyansky, Yuli; et al. (Frontiers in Microbiology, 2022)
Burkholderia pseudomallei and the closely related species, Burkholderia mallei, produce similar multifaceted diseases which range from rapidly fatal to protracted and chronic, and are a major cause of mortality in endemic regions. Besides causing natural infections, both microbes are Tier 1 potential biothreat agents. Antibiotic treatment is prolonged with variable results, hence effective vaccines are urgently needed. The purpose of our studies was to compare candidate vaccines which target both melioidosis and glanders, identify the most efficacious one(s), and define residual requirements for their transition to the non-human primate aerosol model. Studies were conducted in the C57BL/6 mouse model that evaluated the humoral and cell-mediated immune response and protective efficacy of three Burkholderia vaccine candidates against lethal aerosol challenges with B. pseudomallei K96243, B. pseudomallei MSHR5855, and B. mallei FMH. Two vaccines, a capsule conjugate+Hcp1 subunit vaccine and the live B. pseudomallei 668 ∆ilvI strain, provided significant protection and were down-selected for advanced investigation.